ANALISIS KANDUNGAN LOGAM BERAT TIMBAL (Pb) DAN KADMIUM ( Cd) PADA KERANG HIJAU (Perna viridis L.) YANG BEREDAR DI PASAR BADUNG - Anak Agung Istri Mirah Dharmadewi; I Gusti Agung Gede Wiadnyana (Emasains : Jurnal Edukasi Matematika dan Sains, 2019)
This research was conducted to determine the content of heavy metals lead (Pb) and Cadmium (Cd) in green shells circulating in the badung market. Samples of green mussels were taken from the Badung Market, Bali. Then proceed with the analysis of lead content (Pb) and Cadmium (Cd) in the Analytical Laboratory of Udayana University. A sample of green mussels (Perna viridis L.) is opened from the shell to take the meat. Then the sample is mashed by chopped and crushed and put into an erlenmeyer. Each sample was given a repeat of 3 times using factorial pattern CRD. Then proceed with the process of wet ashing (wet digestion). The results showed that the content of heavy metals lead and cadmium in green shells (Perna viridis L.) exceeded the maximum limit of heavy metal contamination. Where the lead heavy metal content (Pb) of shellfish taken at Badung Market is 28.887 mg / kg while the cadmium heavy metal content (Cd) taken at the badung market is 3.15 mg / kg. The results of the analyzed heavy metal content exceed the threshold normal, which has been established by the Food and Drug Supervisory Agency (BPOM)